DESAIN FORMULIR PERSETUJUAN PEMBERIAN SUSU FORMULA PADA BAYI DI RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA - , OKTA SAPUTRA; , Dr. RA. Arida Oetami, M.Kes ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Giving Consent Form on Infant Formula at PKU Muhammadiyah Hospital of Yogyakarta has not been found. The form has been replaced by the register approval of formula feeding in infants. However, items in the register is not fully complete so these registers can not be used as evidence of a strong lawrelated rejection or approval of formula feeding in infants. Objective: Design a consent form formula feeding in infants as evidence of the baby's mother or family consent to the provision of infant formula in infants with medical indications emphasize aspects of the content, physical, and anatomical so it can be used by the parties concerned. Process Design: The design process begins with the determination of an idea and then proceed with the preparation phase of policy analysis and interviews. The next stage of designing the form. Then the presentation of the draft is to propose two alternatives for the form chosen by the respondent. After the draft revised selected form to obtain consent forms embodiment of formula feeding in infants. And then performed tests on 12 forms selected by the nursery nurse. Results: Based on the results of interviews with five respondents stated that consent forms need to be made on infant formula feeding. Then designers collect data to determine the item through interviews and review of regulations governing informed consent, exclusive breastfeeding and the use of infant formula. Then two alternative forms designer to design in accordance with the content aspect, the physical and antomik. Based on the results of interviews with respondents to determine the increments in the form of two design alternatives selected the second alternative form design chosen is a consent form formula feeding in infants second alternative. Form size is 21 x 29.7 cm, using the HVS 80 gr, color logos, body and font items are brown. List of items contained in the form is no medical record, the identity of an approver, family relationships, the statement has received information from the doctor, diagnosis baby's mother, maternal medical indications baby, baby diagnostics, medical indications baby, alternative actions, successes and complications, a statement approved to give formula, the identity of the patient, ward / patient-care areas, where do the approval, the date and time do consent, the name and signature of the treating physician, an approver, family witnesses, and witnesses hospital. Forms elected then tested against 12 existing nursing a baby's room with the results of all nursery nurse agrees with the consent form and formula feeding in infants at PKU Muhammadiyah Hospital of Yogyakarta.